Analysis of Research and Development in Local Wisdom-Based Physics Learning - Arum Wulandari; Jumadi Jumadi (Indonesian Journal of STEM Education, 2025)
This study aims to analyze the research and development (R&D) of local wisdom-based physics learning in Indonesia. This research is a content analysis using a qualitative descriptive approach. After a screening process based on specific criteria, 10 articles were selected for this study. The findings indicate that local wisdom-based physics learning can improve students' learning outcomes. Furthermore, the results show that Indonesian students who utilized local wisdom-based physics learning integrated with technology demonstrated higher academic achievement.